2015
DOI: 10.1093/ofid/ofv052
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Immunity, More Than Aging, Influences Influenza Vaccine Responses

Abstract: Background. Influenza disproportionately impacts older adults while current vaccines have reduced effectiveness in the older population.Methods. We conducted a comprehensive evaluation of cellular and humoral immune responses of adults aged 50 years and older to the 2008–2009 seasonal trivalent inactivated influenza vaccine and assessed factors influencing vaccine response.Results. Vaccination increased hemagglutination inhibition and neutralizing antibody; however, 66.3% of subjects did not reach hemagglutina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
6
45
1
1
Order By: Relevance
“…This is consistent with a previously published report by Reber and colleagues, in which prevaccination titers were the best predictor of postvaccination immunity to influenza among adults older than 50 years of age (13). In fact, those authors found age to be only modestly associated with lower vaccine responses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with a previously published report by Reber and colleagues, in which prevaccination titers were the best predictor of postvaccination immunity to influenza among adults older than 50 years of age (13). In fact, those authors found age to be only modestly associated with lower vaccine responses.…”
Section: Discussionsupporting
confidence: 92%
“…These rates did not differ by frailty status. Our observed rates of seroprotection were similar to findings reported for older adults, including greater immune protection against A(H3N2) (13). Incidentally, among older adults, A(H3N2) virus has been found to be associated with more severe morbidity and increased mortality rates, compared with A (H1N1)pdm09 (2, 3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Virus-specific PBs, also known as Ab-secreting cells (ASCs), were evaluated by an ex vivo enzyme-linked immunospot (ELISPOT) assay as previously described [15]. Briefly, day 0 and day 7 paired sets of PBMCs were directly placed onto A (H3N2) virus-coated ELISPOT plates (100 hemagglutinin units/well) overnight, and ASCs were detected through enzymatic reaction.…”
Section: Assessment Of B-cell and T-cell Responsesmentioning
confidence: 99%
“…Semakin tua usia seseorang, respon imunnya akan semakin buruk. 8 Respon yang berbeda pada usia lanjut ini diperkirakan karena frailty dan kejadian immunosenescense yang mendasarinya. Kejadian frailty ini ternyata cukup sering, Collerton, dkk.…”
Section: Pendahuluanunclassified